Factors affecting non-coverage of measles-rubella vaccination among children aged 9–59 months in Tanzania. Issue 41 (1st October 2021) - Mkopi, Abdallah; Mtenga, Sally; Festo, Charles; Mhalu, Grace; Shabani, Josephine; Tillya, Robert; Masemo, Ame; Kheir, Khamis; Nassor, Mohamed; Mwengee, William; Lyimo, Dafrossa; Masanja, Honorati
Abstract: Globally, measles remains a major cause of child mortality, and rubella is the leading cause of birth defects among all infectious diseases. In 2012, the World Health Assembly endorsed the Global Vaccine Action Plan that set a target to eliminate Measles-Rubella (MR) in five of the six World Health Organization (WHO) regions by 2020. This was cross-sectional study employed both quantitative and qualitative research methods. The sample size was calculated to provide overall, age- and sex-specific coverage estimates for MR vaccine among children aged between 9 and 59 months at the national level. Using desired precision of ±5% with an expected coverage of 95%, a total of 15, 235 households were required. The age of children, a child who had received the MR vaccine before the campaign, household wealth quintile, the age of caregivers, and their marital status were associated with non-coverage of MR vaccination among children aged 9–59 months in Tanzania. Nationally, an estimated 88.2% (95% CI: 87.3–89%) of children aged 9–59 months received the MR campaign dose, as assessed by caregivers' recall. These estimates revealed slightly higher coverage in Zanzibar 89.6% (95% CI: 84.7–93%) compared to Mainland Tanzania 88.1% (95% CI 87.2–88.9%). These associated factors revealed causes of unvaccinated children and may be some of the reasons for Tanzania's failure to meet the MR campaign target of 95 percent vaccination coverage. Thus, vaccine development must increase programmatic oversight in order to improve immunization activities and communication strategies in Tanzanian areas with low MR coverage.